Video Reflection in Discharge Communication Skills Training With Simulated Patients: A Qualitative Study of Nursing Students’ Perceptions - MacLean, S.; Geddes, F.; Kelly, Michelle; Della, Phillip (Elsevier Inc., 2019)
Background: The use of video-assisted reflection as part of the debriefing process is a growing area of interest in simulation-based education. To further develop knowledge in this field, this study explored nursing students’ reflections on their experience and learning after independently viewing audiovisual recordings of themselves engaging in a patient discharge simulation. Methods: A qualitative study design was used. Students demonstrated their discharge communication skills with simulated patients in three learning intervention groups. Each student privately viewed an audiovisual recording of their simulation session before attending a group debriefing. Audio recordings from 35 debriefing sessions were transcribed for both content analysis and thematic analysis. The sample included 141 nursing students enrolled in a Bachelor of Science (Nursing) program. Results: Six themes and four subthemes were identified. Themes were realism, nonverbal communication, verbal communication skills, reflective learning, becoming a nurse, and patient needs. Two word clouds using wordcloud.com were generated from the content analysis of students’ thoughts and feelings about the simulation experience. Conclusion: Using simulated patients and video-assisted reflection when teaching communication skills resulted in students reporting a high level of self-awareness, confidence, and a sense of achievement. Students indicated that the process helped to gain a greater understanding of the importance of effective verbal and nonverbal communication skills during interactions with patients. Students reflected on the importance of engaging with patients and considering their postdischarge needs and well-being as part of discharge communication practises.